Agile O-MaSE: Agent-Oriented Agile Framework - Gominho, Fabiana Ribeiro Ferraz; Costa, Rosa Maria Esteves Moreira da; Werneck, Vera Maria B. (Proceedings of the Workshop-School on Agents, Environments, and Applications (WESAAC); 2020: Proceedings of the 14th Workshop-School on Agents, Environments, and ApplicationsDO - 10.5753/wesaac.2020.33393, 2020)
Agile methods have been proposed to support the development of multiagent system and currently, some methodologies already incorporate this concept. However, they consider only one specific agile approach. The objective of this paper is to present an agile extension incorporated into the O-MaSE method of developing multiagent systems. The framework Agile O-MaSE was built to be used in modern iterative and incremental projects, replacing the traditional cascade approach. Agile O-MaSE maintained characteristics of the standard O-MaSE methodology, adding activities that characterize and control agile iterations, with a set of activities, artifacts, and agile practices. After defining Agile O-MaSE, a pilot study was carried out with the development of an educational medical game geared towards agents. Preliminary results show positive aspects in the composition of Agile O-MaSE's activities.